2017
DOI: 10.1016/j.cortex.2017.08.031
|View full text |Cite
|
Sign up to set email alerts
|

Linking left hemispheric tissue preservation to fMRI language task activation in chronic stroke patients

Abstract: The preservation of near-typical function in distributed brain networks is associated with less severe deficits in chronic stroke patients. However, it remains unclear how task-evoked responses in networks that support complex cognitive functions such as semantic processing relate to the post-stroke brain anatomy. Here, we used recently developed methods for the analysis of multimodal MRI data to investigate the relationship between regional tissue concentration and functional MRI activation evoked during audi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 88 publications
(202 reference statements)
4
29
0
Order By: Relevance
“…In our own previous study in a normal population of proverb comprehension, we reported that the right precuneus and right supramarginal gyrus are involved in abstract language processing (Yi et al, 2017). In our current study, we observed that transcallosal inhibition (Elkana, Frost, Kramer, Ben-Bashat, & Schweiger, 2013;Griffis et al, 2017;Hartwigsen, 2016;Hartwigsen et al, 2010;Hylin et al, 2017;Lim & Kang, 2015) through the right hemisphere might be reduced because right hemisphere stroke patients show a persistent lesion for about 30 days even when the recovery mechanism has begun. The contralateral homologous cortex may be activated when these patients attempt to comprehend an opaque proverb that requires semantic processing.…”
Section: Abstract Language Processing In Patients With Right Mca Insupporting
confidence: 48%
“…In our own previous study in a normal population of proverb comprehension, we reported that the right precuneus and right supramarginal gyrus are involved in abstract language processing (Yi et al, 2017). In our current study, we observed that transcallosal inhibition (Elkana, Frost, Kramer, Ben-Bashat, & Schweiger, 2013;Griffis et al, 2017;Hartwigsen, 2016;Hartwigsen et al, 2010;Hylin et al, 2017;Lim & Kang, 2015) through the right hemisphere might be reduced because right hemisphere stroke patients show a persistent lesion for about 30 days even when the recovery mechanism has begun. The contralateral homologous cortex may be activated when these patients attempt to comprehend an opaque proverb that requires semantic processing.…”
Section: Abstract Language Processing In Patients With Right Mca Insupporting
confidence: 48%
“…SDC measures were defined for each patient based on the intersection of their lesion with a structural connectome atlas constructed with data from healthy individuals (see Methods). Similar atlas-based approaches have been used by other recent lesion studies (Carter et al, 2017;Foulon et al, 2018a;Griffis et al, 2017bGriffis et al, , 2017aHope et al, 2018;Kuceyeski et al, 2013Kuceyeski et al, , 2014Kuceyeski et al, , 2015Kuceyeski et al, , 2016bPustina et al, 2017a;Ramsey et al, 2017), and analogous strategies are often employed to study SC-FC relationships in animal models (Adachi et al, 2011;Grandjean et al, 2017;Grayson et al, 2016;Shen et al, 2015b). While these approaches assume similar approximations of individual structural connectomes by the atlas and cannot account for interindividual variability in the properties of un-damaged fiber pathways (Forkel and Catani, 2018;Forkel et al, 2014), they also offer some protection against potential biases arising from interindividual differences in diffusion MRI data quality, lesion effects on data processing/reconstruction, etc.…”
Section: Limitationsmentioning
confidence: 94%
“…Our results argue against a popular account of FC disruptions in patients with focal brain lesions, namely that most focal lesions selectively disrupt function within damaged functional systems (Nomura et al, 2010;Warren et al, 2014) while lesions affecting FC connector nodes broadly disrupt system organization (Gratton et al, 2012). This account has been highly influential, but it has been challenged by recent evidence indicating that lesions can disrupt FC between undamaged systems while sparing FC within damaged systems (Eldaief et al, 2016), that damage to "connector" regions may not be particularly important for predicting FC disruptions in multivariate GM damage models (Yuan et al, 2017), and that disruptions of task-evoked systems are linked to lesions that minimally overlap with constituent regions but that broadly disrupt withinsystem SC (Griffis et al, 2017a). While we directly replicated the effect of FC connector damage on modularity, adding total parcel SDC information increased the variance explained by a factor of 2.5, and the effect of connector damage did not persist when SDC information was simultaneously modeled (Fig.…”
Section: Structural Correlates Of Functional Connectivity Disruptionsmentioning
confidence: 99%
“…A growing body of evidence highlights the crucial role of the left hemispheric spared areas in aphasia recovery also at chronic stages (53)(54)(55)(56)(57)(58). Functional neuroimaging studies also confirmed that improved speech and language functioning following aphasia treatment relies, at least partly, on the activation of spared regions of the left hemisphere (59)(60)(61)(62).…”
Section: Discussionmentioning
confidence: 92%